Utilization of glycosaminoglycans by the human gut microbiota: participating bacteria and their enzymatic machineries - Parkash Singh Rawat; Ahkam Saddam Seyed Hameed; Xiangfeng Meng; Weifeng Liu (Gut Microbes)
Glycosaminoglycans (GAGs) are consistently present in the human colon in free forms and as part of proteoglycans. Their utilization is critical for the colonization and proliferation of gut bacteria and also the health of hosts. Hence, it is essential to determine the GAG-degrading members of the gut bacteria and their enzymatic machinery for GAG depolymerization. In this review, we have summarized the reported GAG utilizers from Bacteroides and presented their polysaccharide utilization loci (PUL) and related enzymatic machineries for the degradation of chondroitin and heparin/heparan sulfate. Although similar comprehensive knowledge of GAG degradation is not available for other gut phyla, we have specified recently isolated GAG degraders from gut Firmicutes and Proteobacteria, and analyzed their genomes for the presence of putative GAG PULs. Deciphering the precise GAG utilization mechanism for various phyla will augment our understanding of their effects on human health.